The Impact of Digital, Social Media, and Viral Marketing Strategies on Customer Satisfaction and Purchase Decision in Sports Club Products (Third Sector Social Economic Review, 2026)
This study aims to examine the effects of digital marketing, social media marketing, and viral marketing strategies on customer satisfaction and purchase decision regarding sports club products. Using Structural Equation Modeling (SEM), an online survey was conducted with 388 respondents residing in Istanbul who had purchased sports-related products at least three times. Digital marketing, social media marketing, and viral marketing were modeled as independent variables, while customer satisfaction and purchase decision were treated as dependent variables. The analysis revealed that all three marketing strategies had statistically significant and positive effects on both customer satisfaction and purchase decisions. Notably, viral marketing emerged as the most influential strategy on customer satisfaction, whereas social media marketing had the strongest impact on purchase decision. The findings emphasize the decisive role of digital content engagement in shaping consumers’ brand perceptions and purchasing intentions. The results suggest that sports clubs should prioritize consumer engagement in their digital marketing strategies and leverage the power of viral content to enhance customer loyalty. The study highlights the strategic importance of creating shareable and emotionally engaging content, especially in the context of sports fandom and brand identity. Additionally, the findings contribute to both theoretical and practical understandings of how digital platforms influence consumer behavior in the sports marketing domain. This research provides valuable insights for marketing professionals and sports organizations aiming to strengthen their digital presence and improve consumer satisfaction and retention through innovative and data-driven digital strategies.
Keywords: Digital Marketing; Social Media Marketing; Viral Marketing; Customer Satisfaction; Purchase Decision